Relationship between Knowledge of Risk Factor in Pregnancy and Methods of Delivery at RSUD Dr.Moewardi - Permatasari, Ariesta; ., Soetrisno; Murti, Bhisma (Nexus Kedokteran Klinik, 2012)
Background: Maternal mortality in Indonesia is still high. Vaginal delivery with vacuum extraction or forceps may increase the risk of birth canal laseration and postpartum hemorrhage which is a factor of maternal mortality as many as 2.5% to 5%, while the act of caesarean section rate is 14%. Knowledge of pregnant women is hypothesized to affect the success of birth delivery. Less knowledge about risk factor in pregnancy can impact the quality of pregnancy that will determine the process of labor. This study aimed to analyze the relationship between knowledge of risk factor in pregnancy and types of delivery. Methods: This analytic study was observational with cross-sectional approach. A sample of 66 study subjects was selected by fixed-disease sampling from mothers who give birth at RSUD Dr. Moewardi Surakarta in Mei-July 2012. The data were collected by interview using a set of questionnaire and from medical records. The data was analyzed using multiple logistic regression method on Statistical Product and Service Solution (SPSS) version 16.00 for Windows. Results: The study showed that with controlling the counfounding factors such as parity and maternal height, known that lack of knowledge about risk factor in pregnancy is the risk of operative delivery 5.6 times as many level than a good knowledge (OR = 5.60; CI 95% 1.726 hingga 18.170; p = 0.004). Conclusions: There was a statistically significant relationship between knowledge of risk factor in pregnancy and types of delivery. This conclusion was drawn after controlling for the effects of confounding factors such as parity and maternal height. Keywords: Knowledge of Risk Factor in Pregnancy, Types of DeliveryÂ